Competitiveness analysis of Malaysian natural rubber in the world market / Afiff Aizat Mohd Rasdi - Mohd Rasdi, Afiff Aizat (Faculty of Plantation and Agrotechnology, 2017)
Natural rubber (Hevea brasiliensis) is one of the plantation commodities, which plays an important role in the economic development of many countries. Thailand, Indonesia and Malaysia have dominated the supply of natural rubber in the world market. Instead of being a major producing country in the world around years 1970s until the 1980s, Malaysia has lost its position to Thailand and Indonesia. All data used in this study is secondary panel data, which is a combination of time series data. Time series data includes annual data from 1965 to 2015. The data used were collected from FAOSTAT, International Rubber Study Group (IRSG), Department Of Statistics Malaysia, and Malaysian Rubber Board. The method that used to answer the first objective is graph analysis, whereas for the second objective by Revealed Comparative Advantage (RCA) and Herfindahl Hirschman Index (HHI) and for the third objective were measured by Import Deficiency Ratio (IDR) and Self-Sufficiency Ratio (SSR). The result shows that Malaysia has comparative advantage in natural rubber industry is proved by RCA value 1.45 > 1. Meanwhile, HHI value 2832 >1800 showed Malaysian natural rubber industry have a high market concentration in the global market. The average percentage of IDR is 80% - 200% and SSR above 120% showed Malaysian natural rubber industry is relatively more specialized in the natural rubber industry. Based on the research, Malaysia has strong and energized in the rubber industry and dominated 50% market share in the world, which is Malaysia, has high competitiveness level in the rubber industry. As a recommendation, more research is needed to investigate the problems that influence rubber industry in Malaysia.